From general practice to primary care - Iliffe, Steve (Oxford University Press, 2008)
Anxiety about medicine becoming impersonal and mechanised permeates the NHS. In addition, the popular media is full of stories about the health service and its unhappy staff, focusing on the belief that professionals and patients are being turned into assembly-line workers and objects. This is particularly prevalent in general practice, as plans for massive policlinics are revealed and payment systems shift seemingly inexorably towards incentives and targets. The ethos of family medicine, which places so much stress on continuity of care, psychosocial understanding of illness, and the careful management of doubt, is challenged by guidelines, governance, quality frameworks, and patient satisfaction surveys. General practice is being industrialized into primary care, or so it can seem